2015
DOI: 10.1093/intimm/dxv066
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and TLR9 ligands regulate antigen presentation by macrophages

Abstract: The toll-like receptors (TLRs) are important innate receptors recognizing potentially pathogenic material. However, they also play a significant role in the development of Alzheimer's disease, cancer, autoimmunity and the susceptibility to viral infections. Macrophages are essential for an effective immune response to foreign material and the resolution of inflammation. In these studies, we examined the impact of different TLR ligands on macrophage cell function. We demonstrate that stimulation of all TLRs tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…In a recent mouse model TLR7 ligation was shown to increase clearance of apoptotic cells after stimulation of Ly6C + monocytes with a TLR7 ligand in C57BL6 mice [35]. In addition, an in vitro study indicated that TLR7 ligands shift macrophages toward an M2-like long-lived macrophage subtype cell [36]. Taken together, these studies support our finding of TLR7 expression in macrophages with clearing properties.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent mouse model TLR7 ligation was shown to increase clearance of apoptotic cells after stimulation of Ly6C + monocytes with a TLR7 ligand in C57BL6 mice [35]. In addition, an in vitro study indicated that TLR7 ligands shift macrophages toward an M2-like long-lived macrophage subtype cell [36]. Taken together, these studies support our finding of TLR7 expression in macrophages with clearing properties.…”
Section: Discussionsupporting
confidence: 87%
“…Unstimulated DCs from Sle1TLR-9 À/À mouse kidneys induced more T cell proliferation than those from Sle1 controls, which was enhanced with the TLR-7 ligand R848 ( Figure 5C and Supplementary Figure 5A, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40535/ abstract). Renal macrophages did not show augmented T cell proliferation with R848, consistent with earlier data from bone-marrow derived and peritoneal macrophages (40). Both renal DCs and macrophages had increased TLR-7 protein expression in the absence of TLR-9, and the levels positively correlated with the percentage of infiltrating renal DCs and macrophages ( Figures 5D and E).…”
Section: Tlr-9 Regulates Tlr-7 Protein Expression In Lupussupporting
confidence: 90%
“…All but one of the residues under site specific selection seen in TLR7 and TLR9 were located in the ectodomain, which may suggest possible alterations in ligand recognition driven by selection pressure from Y. pestis or other shared pathogens. Stimulation of TLR7 and TLR9 have also been reported to regulate antigen presentation by MHCII in murine macrophages [62]. These data could therefore indicate a possible connection of the selection in TLR7 and TLR9 with the great gerbil duplication in MHCII .…”
Section: Discussionmentioning
confidence: 89%